2019
DOI: 10.3991/ijim.v13i08.9562
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of MALL Instruction in Business English Learning

Abstract: <p><strong> </strong></p><p><strong>T</strong>he existing technological expansion has transformed pervasive revolutions in modern civilization, with continuing innovation of services and products. Nowadays people are having different channels of communication.  Currently, mobile learning (M-learning) is being used extensively in teaching and learning foreign languages which further widens the mobility of learners. The usage of mobile instruction can lead learners towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…On the other hand, the subject of how the co-occurrence of different types of assessment contributes to the improvement of student learning has received less attention, particularly research that focuses on different higher education institutions. Khan, Radzuan, Shahbaz, Ibrahim and Mustafa (2018) asserted that technology is playing its part in the development of language learning and various researchers are using technology in teaching and learning language (Khan, Radzuan, Alkhunaizan, Mustafa, & Khan, 2019;Shahbaz & Khan, 2017); thus the role of continuous assessment is vital. There is a gap in the literature in relation to studies that compare the students from the English Language Department across different higher education institutions on the relationship between assessment and student learning.…”
Section: Background Of the Studymentioning
confidence: 99%
“…On the other hand, the subject of how the co-occurrence of different types of assessment contributes to the improvement of student learning has received less attention, particularly research that focuses on different higher education institutions. Khan, Radzuan, Shahbaz, Ibrahim and Mustafa (2018) asserted that technology is playing its part in the development of language learning and various researchers are using technology in teaching and learning language (Khan, Radzuan, Alkhunaizan, Mustafa, & Khan, 2019;Shahbaz & Khan, 2017); thus the role of continuous assessment is vital. There is a gap in the literature in relation to studies that compare the students from the English Language Department across different higher education institutions on the relationship between assessment and student learning.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Correlation test results showed the statement of the use of mobile phones by students to learn, make the process of learning physics become efficient correlate 0.76 (moderate) with the belief that the use of mobile phones by students and teachers, strengthens and improves the quality of the learning process. This belief is supported by many research findings which state that mlearning strengthens and improves the quality of the learning process (Khan, Radzuan, Alkhunaizan, Mustafa, & Khan, 2019;Mughal, Atkins, Morrow, & Al-Jundi, 2018;Njenga, Oboko, Omwenga, & Maina, 2018).…”
Section: Resultsmentioning
confidence: 74%
“…According to Kiraly (2014), the problem of poor outcomes in the teaching and learning of EFL in the Saudi Kingdom can be blamed on the fact that "the mother tongue is so deeply embedded in our mental lives & inner consciousness that learning the second language requires at first a different reaction to language one that is reorientation and in part a reorganization of consciousness" (P98). In terms of solutions, Khan et al (2019) argue that the issue of ineffective communication can be reduced by the use of technology-based tools such as WhatsApp as means for fostering effective and frequent practicing with communicating in English by EFL learners. Other possible ways to reduce the intensity of ineffective communication is engaging learners with group conversations, as reliable platforms for enabling students to convey their messages easily and learning in the process (Lunenburg, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result of such is a situation in which students are forced to unduly struggle to maintain focus on the subject matter (Khan, et al, 2018a). Numerous studies have indicated on the critical role that modern technology has as a critical determinant of the nature of communication in the modern classroom (Khan et al, 2019;Khan, et al, 2018a;Khan, et al, 2018b;Shahbaz, et al, 2016;Shahbaz & Khan, 2017). To this end, there are a variety of issues to blame for ineffective communication between teachers and students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation